Post-treatment technologies for integrated algal pond systems - Westensee, Dirk Karl (Rhodes University, Faculty of Science, Institute for Environmental Biotechnology, 2015)
Integrated Algae Pond Systems (IAPS) are a derivation of the Oswald designed Algal Integrated Wastewater Pond Systems (AIWPSÂ®) and combine the use of anaerobic and aerobic bioprocesses to effect wastewater treatment. IAPS technology was introduced to South Africa in 1996 and a pilot plant designed and commissioned at the Belmont Valley WWTW in Grahamstown. The system has been in continual use since implementation and affords a secondarily treated water for reclamation according to its design specifications which most closely resemble those of the AIWPSÂ® Advanced Secondary Process developed by Oswald. As a consequence, and as might be expected, while the technology performed well and delivered a final effluent superior to most pond systems deployed in South Africa it was unable to meet The Department of Water Affairs General Standard for nutrient removal and effluent discharge. The work described in this thesis involved the design, construction, and evaluation of several tertiary treatment units (TTU') for incorporation into the IAPS process design. Included were; Maturation Ponds (MP), Slow Sand Filter (SSF) and Rock Filters (RF). Three MP's were constructed in series with a 12 day retention time and operated in parallel with a two-layered SSF and a three-stage RF. Water quality of the effluent emerging from each of these TTU's was monitored over a 10 month period. Significant decreases in the chemical oxygen demand (COD), ammonium-N, phosphate-P, nitrate-N, faecal coliforms (FC) and total coliforms (TC) were achieved by these TTU's. On average, throughout the testing period, water quality was within the statutory limit for discharge to a water course that is not a listed water course, with the exception of the total suspended solids (TSS). The RF was determined as the most suitable TTU for commercial use due to production of a better quality water, smaller footprint, lower construction costs and less maintenance required. From the results of this investigation it is concluded that commercial deployment of IAPS for the treatment of municipal sewage requires the inclusion of a suitable TTU. Furthermore, and based on the findings presented, RF appears most appropriate to ensure that quality of the final effluent meets the standard for discharge.
Keywords: Sewage disposal plants -- South Africa -- Grahamstown; Water -- Purification -- Filtration; Water -- Purification -- Slow sand filtration; Sewage -- Purification -- Anaerobic treatment; Sewage -- Purification -- Biological treatment; Algae -- Biotechnology